In abstinent MDMA users the cortisol awakening response is off-set but associated with prefrontal serotonin transporter binding as in non-users. (August 2014) - Frokjaer, Vibe Gedsoe; Erritzoe, David; Holst, Klaus Kähler; Madsen, Kathrine Skak; Fisher, Patrick MacDonald; Madsen, Jacob; Svarer, Claus; Knudsen, Gitte Moos
Abstract Serotonergic signaling is considered critical for an appropriate adaptation to stress. We have previously observed that in healthy volunteers, prefrontal serotonin transporter (SERT) binding is positively associated with hypothalamic-pituitary-adrenal (HPA)-axis output in terms of the cortisol awakening response (CAR). Here, we tested (1) if such a correlation persists in a human model of chronic serotonin depletion, namely in 3, 4-Methylenedioxymethamphetamine (MDMA or 'Ecstasy') users, and (2) if CAR differed between MDMA users (N = 18) and non-using healthy volunteers (N = 32). Participants underwent SERT brain imaging with [11C]DASB-PET, and performed home-sampling of CAR, defined as the area under curve with respect to cortisol increase from awakening level. When adjusting for age and group, CAR was positively coupled to prefrontal SERT binding (p = 0.006) and MDMA users showed significantly higher CAR than the control group (p = 0.0003). In conclusion, our data confirm the recently described positive association between prefrontal SERT binding and CAR, this time in a human model of serotonin deficiency. Also, we find that CAR was higher in MDMA users relative to non-users. We suggest that the inhibitory control on HPA-axis output is less efficient in the off-balance state established by recent MDMA use, most likely through mechanisms other than those that can be compensated by lowering SERT levels.